The relationship of patient satisfaction level with word of mouth on health services: systematic review - Fannya, Puteri; Putra, Daniel Happy; Dewi, Deasy Rosmala (International Journal Of Community Medicine And Public Health, 2022)
Health services, especially in hospitals, are now increasingly required to provide excellent service to patients. One of easy way for patients to get information about services is to ask someone who has received the same service before. This is called word of mouth (WOM). This research was conducted using the literature review method. The data was synthesized by comparing 5 literatures that met the inclusion and exclusion criteria. The database sources were Google scholar and PubMed. Data is processed and presented in tabulated form. From 5 literatures that have been reviewed, there were 4 articles stating that there was a significant relationship between patient satisfaction and WOM on health services. The smallest significance number is =0.000, and the largest coefficient value is 0.533, which means that the increasing of patient satisfaction unit will cause a change in WOM to health services by 53.3%. There is only 1 article that finds that there is no relationship between patient satisfaction and WOM with a value of 0.117. There is a significant relationship between patient satisfaction and WOM on health services. Health services such as hospitals should pay attention to patient satisfaction, because it greatly affects the image of the hospital in customer’s point of view.